P037 Indigenous Australians' conceptualisation of sleep health differs from western interpretations. (7th October 2021) - Fatima, Y; King, S; Solomon, S; Bucks, R; Skinner, T
Abstract: Purpose: Despite a significant burden of poor sleep, Aboriginal and Torres Strait Islander peoples' (Indigenous Australians) conceptualisation of sleep health is poorly understood. This research explored Indigenous Australians' understanding and interpretation of sleep health and how that affects their health. Methods: Indigenous people from remote Queensland were invited to participate in focus group discussions exploring their understanding of sleep health, the link between dreaming and sleep, and perceived implications of poor sleep. Participants were also asked to complete an adapted pictorial Epworth Sleepiness Scale (ESS). Descriptive statistics were used to summarise ESS data and participants' demographic data. Thematic analysis was used to analyse focus group data. Results: A total of 29 Indigenous Australians (82% females), median age 39 years (Interquartile range 26–51 years) from various geographical areas within North West Queensland participated in focus group discussions (n=6). The following themes emerged from the data: interconnection among sleep, emotional and physical health; challenges and successes in obtaining healthy sleep; the impact of dreams on waking life; and lack of support from health services in managing sleep issues. Scores from the modified pictorial scale indicate 24% of the participants had excessive daytime sleepiness (ESS score>10 points). Conclusion: Indigenous Australians' conceptualisation of sleep health is different from the western interpretation of sleep health. In particular, the connection between dreams and sleep is not adequately captured in current tools and resources to promote sleep health. This will limit effective prevention and management of sleep issues in Indigenous communities.